Variation in SARS‐CoV‐2 Prevalence in U.S. Skilled Nursing Facilities. Issue 10 (21st August 2020) - White, Elizabeth M.; Kosar, Cyrus M.; Feifer, Richard A.; Blackman, Carolyn; Gravenstein, Stefan; Ouslander, Joseph; Mor, Vincent
Abstract : OBJECTIVE: To identify county and facility factors associated with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) outbreaks in skilled nursing facilities (SNFs). DESIGN: Cross‐sectional study linking county SARS‐CoV‐2 prevalence data, administrative data, state reports of SNF outbreaks, and data from Genesis HealthCare, a large multistate provider of post‐acute and long‐term care. State data are reported as of April 21, 2020; Genesis data are reported as of May 4, 2020. SETTING AND PARTICIPANTS: The Genesis sample consisted of 341 SNFs in 25 states, including a subset of 64 SNFs that underwent universal testing of all residents. The non‐Genesis sample included all other SNFs (n = 3, 016) in the 12 states where Genesis operates that released the names of SNFs with outbreaks. MEASUREMENTS: For Genesis and non‐Genesis SNFs: any outbreak (one or more residents testing positive for SARS‐CoV‐2). For Genesis SNFs only: number of confirmed cases, SNF case fatality rate, and prevalence after universal testing. RESULTS: One hundred eighteen (34.6%) Genesis SNFs and 640 (21.2%) non‐Genesis SNFs had outbreaks. A difference in county prevalence of 1, 000 cases per 100, 000 (1%) was associated with a 33.6 percentage point (95% confidence interval (CI) = 9.6–57.7 percentage point; P = .008) difference in the probability of an outbreak for Genesis and non‐Genesis SNFs combined, and a difference of 12.5 cases per facility (95% CI = 4.4–20.8 cases; P = .003) for Genesis SNFs. A 10‐bed difference in facility size was associated with a 0.9 percentage point (95% CI = 0.6–1.2 percentage point; P  < .001) difference in the probability of outbreak. We found no consistent relationship between Nursing Home Compare Five‐Star ratings or past infection control deficiency citations and probability or severity of outbreak. CONCLUSIONS: Larger SNFs and SNFs in areas of high SARS‐CoV‐2 prevalence are at high risk for outbreaks and must have access to universal testing to detect cases, implement mitigation strategies, and prevent further potentially avoidable cases and related complications. J Am Geriatr Soc 68:2167–2173, 2020. Abstract : See related Special Article by Ouslander et al . in this issue.